Stresses and relative stiffness of the head cover bolts in a pump turbine. (March 2019) - Luo, Yongyao; Chen, Funan; Chen, Liu; Wang, Zhengwei; Yu, Jixing; Luo, Chengzong; Zhao, Zhiwen; Ren, Shaocheng; Li, Jinwei; Deng, Dezhi
Abstract: The stresses and relative stiffness of the head cover bolts in a pump turbine have been calculated using ANSYS. In the numerical model established, the head cover, stay ring and bolts have been included. Results show that the bolts bend due to the preload and the hydraulic pressure acting on the head cover. Consequently, stresses in the mid sections of the bolts are uneven. It is also found that the relative stiffness of the bolts and flange vary with the working condition and preload, which indicates that the whole model including the bolts is a nonlinear system. Therefore, this study concludes that the relative stiffness of the bolts and flange for pump turbines should not be assumed to be a constant value at the design stage.